The challenges of school reform : implementation, impact, and sustainability - Solmon, Lewis C.; Agam, Kimberly Firetag; Priagula, Citadelle (The Milken Family Foundation series on education policy, 2006)
This work expands on the ideas and themes discussed in the first two volumes in this series on education policy: The first book -- Talented Teachers: The Essential Force for Improving Student Achievement -- examines the importance of teacher quality. Years of research have repeatedly confirmed what we inferred to be true--outside of the home environment, the quality of a student's teacher has the strongest impact on learning. After talented teachers were found to be a powerful component for bettering education, the second book -- Improving Student Achievement: Reforms that Work -- introduces reform ideas and programs that positively impact both teacher quality and student work. Now, The Challenges of School Reform: Implementation, Impact, and Sustainability deepens these discussions by exploring the answers to questions regarding ensuring the longevity and sustained success of effective school reform.